Mutation Screening of Exons 7 and 13 of the TMC1 Gene in Autosomal Recessive Non-syndromic Hearing Loss (ARNSHL) in Iran - Moradipour, Negar (Iran Red Crescent Med J, 2016)
BACKGROUND: Non-syndromic hearing loss (NSHL) is the most common birth defect and occurs in approximately 1/1,000 newborns. NSHL is a heterogeneous trait and can arise due to both genetic and environmental factors. Mutations of the transmembrane channel-like 1 (TMC1) gene cause non-syndromic deafness in humans and mice. OBJECTIVES: The aim of the present study was to investigate the association of TMC1 gene mutations of the locus DFNB7/11 in exons 7 and 13 in a cohort of 100 patients with hearing loss in Iran using polymerase chain reaction–single-stranded conformation polymorphism (PCR-SSCP), heteroduplex analysis (HA), and DNA sequencing. PATIENTS AND METHODS: In this experimental study, the blood samples of 100 NSHL patients were collected from 10 provinces in Iran. These patients had a mean age of 16.5 ± 2.01 years and 74.15% of their parents had consanguinity. DNA was extracted from specimens and mutations of exons 7 and 13 of the TMC1 gene were investigated using PCR-SSCP. All samples were checked via HA reaction and suspected specimens with shift bands were subjected to DNA sequencing for investigation of any gene variation. RESULTS: In this study, no mutation was found in the two exons of TMC1 gene. It was concluded from these results that mutations of the TMC1 gene’s special exons 7 and 13 have a low contribution in patients and are not great of clinical importance in these Iranian provinces. CONCLUSIONS: More studies are needed to investigate the relationship between other parts of this gene with hearing loss in different populations through the country. More research could clarify the role of this gene and its relation with deafness and provide essential information for the prevention and management of auditory disorders caused by genetic factors in the Iranian population.